Penyuluhan Kesehatan untuk Meningkatkan Pengetahuan tentang Anemia pada Remaja - Alda Nurani Asmara; Andini Zharfa Asmarani; Desry; Dina Mega Tresna Pamungkas (Yayasan Inspirasi El Burhani, 2022)
Introduction: Anemia is a condition with hemoglobin, hematocrit and red blood cell levels that are lower than normal values. Iron deficiency anemia can cause various impacts on adolescent girls, including lowering the body's resistance so that it is susceptible to disease, decreased activity and learning achievement. Anemia occurs due to lack of iron so that the formation of red blood cells and other functions in the body is disrupted. Adolescent girls are more prone to anemia risk than boys, because young girls have the possibility of losing more iron (Fe) during menstruation. The content of Fe tablets is an important element in the formation of red blood cells. Objective: The purpose of this health education is to increase knowledge about anemia and assist in early prevention of anemia cases among adolescents. Method: The method used in this activity is the question and answer method where this activity begins with finding the target or subject of counseling. Result: Based on the results of research conducted on 25 respondents on January 20, 2022 at SMP Negeri 1 Sadananya, it was found that the subjects did not know about anemia. but the subjects had normal menstrual patterns, never had a history of disease, but the consumption pattern of Fe tablets in all respondents (100%) was irregular. Conclusion: In accordance with the results of the evaluation of the counseling activity on anemia among adolescents, it has been successful with indicators of Knowledge, Problem Solving, participation, duration, and Punctuality.